The scientific conference "Birds of the cities" Zielona Góra, 14-16 September 2012 - Jerzak, Leszek; Ciebiera, Olaf; Bocheński, Marcin (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
All participants found the meeting to be important and worthwhile and spent in a nice and pleasant atmosphere. Once more one could see that birds in the cities constitute a challenge for modern researchers and environmental protectors.
Keywords: wróblowe; ornitologia